A multi-type artifact framework for cyber–physical, social systems design and development - Zakaria Maamar (17246311) (2023)
This paper discusses the design and development of cyber–physical, social systems using a set of guidelines that capture the conceptual and technical characteristics of such systems. These guidelines are packaged into a framework that resorts to the concept of artifact. Because of these characteristics, the framework’s artifacts are specialized into 3 types referred to as data, thing, and social, all connected together through a set of situational relations referred to as work-with-me, work-for-me, back-me, and avoid-me. To mitigate conflicts blue that could arise because of artifacts’ respective time availabilities when they jointly participate in situational relations, policies are put in place defining who does what, when, where, and why. To demonstrate the technical doability of the multi-type artifact framework, a system capturing cyber, physical, and social interactions in a healthcare case-study is developed, deployed, and evaluated. Other Information Published in: Internet of Things License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.iot.2023.100820